Solar Vapor Generation: Extremely Cost‐Effective and Efficient Solar Vapor Generation under Nonconcentrated Illumination Using Thermally Isolated Black Paper (Global Challenges 2/2017). Issue 2 (February 2017) - Liu, Zhejun; Song, Haomin; Ji, Dengxin; Li, Chenyu; Cheney, Alec; Liu, Youhai; Zhang, Nan; Zeng, Xie; Chen, Borui; Gao, Jun; Li, Yuesheng; Liu, Xiang; et al.
Abstract : The shortage of freshwater and sanitation is one of the most pervasive challenges afflicting people throughout the world. It is essential to develop technologies for disinfection and decontamination of water, and to increase water supplies through economic and sustainable ways. Dr. Qiaoqiang Gan's group developed an efficient system utilizing extremely low‐cost carbon‐based materials to realize simultaneous vapor generation and water purification to produce drinking water for personal use. The cover image conceptually illustrates the impact of the proposed system in addressing global freshwater shortages. More details can be found in the article number 1600003 by Zhejun Liu, Haomin Song, Dengxin Ji, Chenyu Li, Alec Cheney, Youhai Liu, Nan Zhang, Xie Zeng, Borui Chen, Jun Gao, Yuesheng Li, Xiang Liu, Diana Aga, Suhua Jiang, Zongfu Yu, and Qiaoqiang Gan*.